“I felt I’d come home”: Sylvia Plath and France - Julie IRIGARAY (E-REA)
This article will use a wide range of material to understand Sylvia Plath’s rich relationship with French culture, from her short stories to her articles for magazines, to her and Ted Hughes’s poems about France. Over the course of a year, Plath took no fewer than four trips to the French capital. Previous publications almost exclusively focused on Plath’s time in Paris (Dave Haslam 2020), but she explored other parts of France and deeply engaged with French culture, so much so that she had planned to move to this country at some stage. Plath travelled to regions as diverse as Brittany and Dordogne, northern France and the Côte d’Azur, and Normandy. Almost all these places inspired a text (“Finisterre”, “Stars Over the Dordogne”, “Berck-Plage”, “The Matisse Chapel”). Plath’s passion for France found its expression in her passion for the arts, from cinema to painting, and of course literature. Her reading of French literature has been widely overlooked by scholars, despite the fact that a poem like “Pursuit” directly quotes Jean Racine. This paper seeks to rectify this by analysing Plath’s French literature books held in her archives.